Analisis Kriteria Penyelesaian Konflik Dan Rumusan Kebijakan Konflik Menggunakan Metode Analytical Heirarchy Process Di Kecamatan Tanah Merah Kabupaten Indragiri Hilir Provinsi Riau - Wahyudi, Bambang; Fanny Septya; Kausar (Jurnal Ekonomi Pertanian dan Agribisnis, 2024)
In providing justice to each party, especially from the community related to land grabbing by the company, by formulating solutions. This research wants to see two things, namely conflict resolution criteria and the formulation of community and company conflict policies in Tanah Merah District, Indragiri Hilir Regency, Riau Province. The data analysis used in this research is Analytical Hierarchy Proces (AHP). The results of this study are the application of mediation, negotiation is a resolution applied to the problem of returning economic value. mediation is an alternative applied to the problem of land carrying capacity with the company dialog facility being a resolution to create a conducive social by building communication between the community and the company. The first rank of the dominant alternative chosen by key informants is mediation with a value of 0.386403018, and the second rank is negotiation with a value of 0.385386325, and the third rank is arbitration with a value of 0.114540671 and the last is dialog facilities with a value of 0.113669958 with the reasons that have been listed from each Analytical Hierarchy Process calculation.